Everyday territories: homelessness, outreach work and city space. (18th July 2017) - Smith, Robin James; Hall, Tom
Abstract: This article develops a situational approach to understanding urban public life and, in particular, the production of urban territories. Our aim is to examine the ways in which city space might be understood as comprising multiple, shifting, mobile and rhythmed territories. We argue that such territories are best understood through attending to their everyday production and negotiation, rather than handling territory as an a priori construct. We develop this argument from the particular case of the street‐level politics of homelessness and street care. The experience of street homelessness and the provision of care in the public spaces of the city is characterised by precarious territorial claims made and lost. We describe some of the ways in which care work with rough sleepers is itself precarious; 'homeless', in lacking a distinct setting in which it might get done. Indeed, outreach work takes place within and affirms homeless territories. The affirmation of territory is shown to be central to the relationship developed between the workers and their rough sleeping clients. We also show, however, the ways in which outreach workers operate on territory not their own, twice over . Outreach work is precarious in that it is practised within, and can run counter to, other territorial productions in which the experience of urban need and the work and politics of care are entangled. In sum, this article aims to move beyond static and binary understandings by developing a mobile and situational approach to city space which recognises the intensive yet overlooked work of territorial production.